The Role of Early Childhood Teachers in Dealing with Autistic Children at Autiscare Snec - Rizky Amelia Putri (Research Psychologie, Orientation et Conseil, 2024)
The main problem in this study is the presence of children who experience autistic disorders at the Autiscare Snec school. Children who have autism aged 8 years are classified as having moderate autism and experience three disorders, namely interaction disorders, communication disorders, and behavior disorders. The purpose of this study was to see the role of early childhood teachers in dealing with autistic children. This research uses qualitative methods with a case study approach to reveal and describe a situation/case by directly observing and interviewing about the role of early childhood teachers in dealing with autistic children in Autiscare Snec. The subject in this study was one child who had an autistic disorder. The source of data in this study is Early Childhood Teachers and Curriculum Representatives at Snec Autiscare School. The data collection techniques used are observation, interviews, and documentation. For the technique of checking the validity of the data, researchers use triangulation. The results obtained from research at the Snec Autiscare School show that the role of teachers in dealing with autistic children can be seen in teachers who are able to guide and teachers who try to develop children's ability to communicate both ways. Teachers are able to implement a pleasant learning atmosphere for children and facilitate all children's needs for smooth learning while at school, such as learning media. The teacher tries to cause or bring up a child's desire by motivating the child and asking about the child's desire or aspiration. After the teacher knows the answer from the child, the teacher gives praise or reward.